Manufacturers and retailers in the global economy. (May 2016) - Raff, Horst; Schmitt, Nicolas
Abstract: We develop a model with multi‐product retailers acting as intermediaries between manufacturers and consumers. We show that the rise in retailer product assortment, the rise of up‐front payments in many retail markets and the observed shift in employment from manufacturing to retailing may be the consequence of the global integration of product markets. We also identify a novel benefit from market integration consisting of efficiency gains in the vertical distribution chain.